Smart Automatic Feed : Sistem Pakan Otomatis Pada Kandang Peternak Ayam - Lalu Delsi Samsumar; Salman Salman; Rudi Muslim; Ardiyallah Akbar (Lembaga Pengembangan Kinerja Dosen, 2023)
Many people use the livestock industry, especially chicken farming, where raising chickens has many benefits, namely being able to produce eggs and meat. The existence of IoT allows communication of all objects via the internet, this can be used to simplify the process of feeding livestock chickens. The method used is the prototype method where prototyping is the first step in developing software or systems, namely having the stages of Needs Analysis, Rapid Design, Building a Prototype, Evaluation of Initial Use, Improving the Prototype, Implementation, and Maintenance. This research aims to build a feeding system with Internet of Things-based automation to maximize feeding and minimize obstacles in providing animal feed to improve the quality of livestock products. Development of Smart Automatic Feed: This Internet of Things (IoT)-based Automatic Feeding System for Chicken Farmers can provide feed via a mobile application and automatically on a scheduled basis and can also monitor the status of feed supplies.